A European Agenda for Smart Consumer Protection Rules for Digital Services - Alexandre de Streel (Intereconomics, 2017)
Digital services are increasingly important in the economy and in society in general, as they continue to shift from being a specific sector of activities to becoming the basis for the provision of most services. They offer multiple new opportunities from which consumers benefit daily, but they also raise novel questions for consumer protection.
Keywords: 330